Red Supergiant Problem Viewed from the Nebular Phase Spectroscopy of Type II Supernovae - Qiliang Fang; Takashi J. Moriya; Keiichi Maeda (The Astrophysical Journal)
The red supergiant (RSG) problem refers to the observed dearth of luminous RSGs identified as progenitors of Type II supernovae (SNe II) in pre-SN imaging. Understanding this phenomenon is essential for studying pre-SN mass loss and the explodability of core-collapse SNe. In this work, we reassess the RSG problem using late-phase spectroscopy of a sample of 50 SNe II. The [O I ] λλ 6300,6363 emission in the spectra is employed to infer the zero-age main-sequence (ZAMS) mass distribution of the progenitors, which is then transformed into a luminosity distribution via an observation-calibrated mass–luminosity relation. The resulting luminosity distribution reveals an upper cutoff at ${log}\,L/L_{\odot }\,=\,5.2{1}_{-0.07}^{+0.09}\,$ dex, and the RSG problem is statistically significant at the 2 σ –3 σ level. Assuming single RSG progenitors that follow the mass–luminosity relation of KEPLER models, this luminosity cutoff corresponds to an upper ZAMS mass limit of $20.6{3}_{-1.64}^{+2.42}\,M_{\odot }$ . Comparisons with independent measurements, including pre-SN imaging and plateau-phase light curve modeling, consistently yield an upper ZAMS mass limit below ∼25 M _⊙ , with a significance level of 1 σ –3 σ . While each individual method provides only marginal significance, the consistency across multiple methodologies suggests that the lack of luminous RSG progenitors may reflect a genuine physical problem. Finally, we discuss several scenarios to account for this issue should it be confirmed as a true manifestation of stellar physics.